(untitled) (Research, Society and Development, 2024)
The present study aims to evaluate the effectiveness of pimavanserin in patients with psychosis in Parkinson’s disease. Its effects on the clinical picture of psychosis were evaluated, as well as its adverse reactions and influences on patients’ quality of life. This is a Systematic Literature Review of a qualitative nature, with a search strategy for the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and Critical Appraisal Skill Program (CASP) methodological evaluation, analyzing a total of 8 articles. Articles were searched in PubMed databases, excluding simple literature reviews and incomplete articles. Those published in the last 10 years (2013-2023) and available in English were included. After a systematic analysis of the studies, it is concluded that pimavanserin demonstrates effectiveness in reducing hallucinogenic and delusional symptoms. Furthermore, it was found that the combination of pimavanserin with other medications, especially clozapine, showed promise in terms of safety, especially in improving cognitive functions. Patients showed improvements in the quality of sleep and wakefulness, in addition to a significant reduction in symptoms. Furthermore, side effects include pneumonia, episodes of syncope, obstructive pulmonary disease, pulmonary embolism and deep vein thrombosis. It is expected that future studies will continue to develop more intervention research on the effectiveness of the medication in treating Parkinson’s disease, highlighting benefits and improvements in patients’ quality of life through the use of the drug in medical practice.